Small airway dysfunction links asthma severity with physical activity and symptom control - Abdo, Mustafa; Trinkmann, Frederik; Kirsten, Anne-Marie; Pedersen, Frauke; Herzmann, Christian; Mutius, Erika von; Kopp, Matthias; Hansen, Gesine; Waschki, Benjamin; Rabe, Klaus F.; Watz, Henrik; Bahmer, Thomas (The journal of allergy and clinical immunology. In practice, 2021)
Background - Little is known about the role of small airway dysfunction (SAD) and its complex relation with asthma control and physical activity (PA). - Objective - To investigate the interrelations among SAD, risk factors for asthma severity, symptom control, and PA. - Methods - We assessed SAD by impulse oscillometry and other sophisticated lung function measures including inert gas washout in adults with asthma (mild to moderate, n = 140; severe, n = 128) and 69 healthy controls from the All Age Asthma Cohort. We evaluated SAD prevalence and its interrelation with risk factors for asthma severity (older age, obesity, and smoking), type 2 inflammation (sputum and blood eosinophils, fractional exhaled nitric oxide), systemic inflammation (high-sensitivity C-reactive protein), asthma control (AC), and PA (accelerometer for 1 week). We applied a clinical model based on structural equation modeling that integrated causal pathways among these clinical variables. - Results - The prevalence of SAD ranged from 75% to 90% in patients with severe asthma and from 53% to 64% in mild to moderate asthma. Severe SAD was associated with poor AC and low PA. Structural equation modeling indicated that age, obesity, obesity-related systemic inflammation, T2 inflammation, and smoking are independent predictors of SAD. Small airway dysfunction was the main determinant factor of AC, which in turn affected PA. Obesity affected AC directly and through its contribution to SAD and low PA. In addition, PA had bidirectional associations with obesity, SAD, and AC. Structural equation modeling also indicated interrelations among distal airflow limitation, air trapping, and ventilation heterogeneity. - Conclusions - Small airway dysfunction is a highly prevalent key feature of asthma that interrelates a spectrum of distal lung function abnormalities with risk factors for asthma severity, asthma control, and physical activity.